2020
DOI: 10.1186/s12943-020-01287-2
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: functions and mechanisms in colon cancer

Abstract: Evidence indicates that long non-coding RNAs (lncRNAs) play a crucial role in the carcinogenesis and progression of a wide variety of human malignancies including colon cancer. In this review, we describe the functions and mechanisms of lncRNAs involved in colon oncogenesis, such as HOTAIR, PVT1, H19, MALAT1, SNHG1, SNHG7, SNHG15, TUG1, XIST, ROR and ZEB1-AS1. We summarize the roles of lncRNAs in regulating cell proliferation, cell apoptotic death, the cell cycle, cell migrative and invasive ability, epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 89 publications
2
152
0
Order By: Relevance
“…Cancer cells aquire drug resistance through different mechanisms ( Chen and Shen, 2020 ; da Costa and Baiocchi, 2020 ; Qin et al, 2020 ; Zhu et al, 2020 ; Pastushenko et al, 2021 ), including enhancement of oxygen free radical scavenging, promotion of DNA damage repair, or inhibition of apoptotic signaling pathway activation ( Lü et al, 2008 ; Bakkenist et al, 2018 ; Phi et al, 2018 ). In vitro studies suggest a role for SOX9 in regulating cell differentiation in the intestinal epithelium ( Mori-Akiyama et al, 2007 ; Aguilar-Medina et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells aquire drug resistance through different mechanisms ( Chen and Shen, 2020 ; da Costa and Baiocchi, 2020 ; Qin et al, 2020 ; Zhu et al, 2020 ; Pastushenko et al, 2021 ), including enhancement of oxygen free radical scavenging, promotion of DNA damage repair, or inhibition of apoptotic signaling pathway activation ( Lü et al, 2008 ; Bakkenist et al, 2018 ; Phi et al, 2018 ). In vitro studies suggest a role for SOX9 in regulating cell differentiation in the intestinal epithelium ( Mori-Akiyama et al, 2007 ; Aguilar-Medina et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the clinical relationship between lncRNAs and human cancer is a research hotspot in tumour molecular biology given their importance in tumorigenesis and tumour development [23][24][25]. Therefore, lncRNAs may be attractive therapeutic targets for tumour intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Wnt-targeting therapeutics in other cancer types are in different phases of pre-clinical or early clinical trials, while those for osteosarcoma are still scarcely observed [ 6 , 41 ]. Recently, lncRNAs are gaining researchers’ attention as an alternative strategy for cancer treatment [ 22 , 183 , 184 ]. The increasing insights into the crosstalk between lncRNAs and Wnt in osteosarcoma may lead to the development of promising pharmacological candidates (Shown in Fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…LncRNAs could participate in diverse biological processes, including cell survival, apoptosis, differentiation, DNA damage repair, and inflammation [ 21 ]. Mechanistically, the most commonly reported feature of lncRNAs is to act as a competing endogenous RNA (ceRNA) to regulate miRNA expression and thus to target downstream genes [ 22 ]. Besides, lncRNAs could also interact with macromolecules such as DNA, RNA and proteins to modulate expression of target genes at transcriptional, posttranscriptional and translational level, providing for multiple layers of control, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%